Prevention and treatment of human immunodeficiency virus/acquired immunodeficiency syndrome in resource-limited settings - Daniel R. Hogan; Joshua A. Salomon (The World Health Organization, 2005)
Strategies for confronting the epidemic of human immunodeficiency virus/acquired immunodeficiency syndrome (HIV/AIDS) have included a range of different approaches that focus on prevention and treatment. However, debate persists over what levels of emphasis are appropriate for the different components of the global response. This paper presents an overview of this debate and briefly summarizes the evidence on a range of interventions designed to prevent the spread of HIV infection, paying particular attention to voluntary counselling and testing, treatment for sexually transmitted infections and prevention of mother-to-child transmission. We also review the experience with antiretroviral therapy to date in terms of response rates and survival rates, adherence, drug resistance, behavioural change and epidemiological impact. Although various studies have identified strategies with proven effectiveness in reducing the risks of HIV infection and AIDS mortality, considerable uncertainties remain. Successful integration of treatment and prevention of HIV/AIDS will require a balanced approach and rigorous monitoring of the impact of programmes in terms of both individual and population outcomes.